Current perspectives and new directions in mechanics, modelling and design of structural systems : proceedings of the Eighth International Conference on Structural Engineering, Mechanics and Computation, 5-7 September 2022, Cape Town, South Africa /: proceedings of the Eighth International Conference on Structural Engineering, Mechanics and Computation, 5-7 September 2022, Cape Town, South Africa. (2022) - Unknown
No abstract available